Comparison of cutting tool geometries based on cutting forces and roughness of hard turned surfaces - Molnár, Viktor; Szabo, Gergely (Національний технічний університет "Харківський політехнічний інститут", 2024)
Surface quality and energy consumption are two widely studied topics of hard machining. Due to the increasing need of companies for new, more efficient materials, tools and procedures, their manufacturers or suppliers have to deliver innovative solutions from time to time. In this study the latest development of a hard turning insert manufacturer is used in comprehensive machining experiments to show how the new tool (a wiper insert) behaves compared to its standard counterpart. Based on surface roughness and machining force measurement and analysis, this efficiency is proved by quantitative results: the wiper geometry ensures significantly better surface quality, while the energy consumption of the used machine tool is considerably lower.

У токарній обробці загартованих сталей ріжучі інструменти постійно розробляються їх виробниками, і широкий спектр застосування охоплюється різними рішеннями, що стосуються інструментальних матеріалів або геометрії. У цьому дослідженні представлені результати експерименту з механічної обробки. Вимірювали та аналізували шорсткість оброблюваних циліндричних поверхонь та зусилля обробки. Механічна обробка здійснювалася стандартною вставкою, а потім її аналогом після доводки. Мета полягала в тому, щоб визначити,чи забезпечує вставка після доводкименше енергоспоживання за рахунок менших сил різання та сприятливу якість поверхні за рахунок нижчих значень шорсткості поверхні.
Порівняння геометрії ріжучого інструменту на основі сил різання і шорсткості точених поверхонь
Keywords: surface topography; cutting force; hard turning; wiper geometry; surface quality; energy consumption; рельєф поверхні; сила різання; жорстке токарне оброблення; технологічні дані